Deciphering correlation between permeability and size of anammox granule: "pores as medium". (1st March 2021) - Xu, Dongdong; Fan, Jiahui; Li, Wenji; Chen, Wenda; Pan, Chao; Kang, Da; Li, Yiyu; Shan, Shengdao; Zheng, Ping
Highlights: Pore structure of anammox granule was characterized with Micro-CT. Pore distribution was observed to vary largely with increase of granule size. Permeability was revealed to correlate negatively with granule size. Permeability was found to deteriorate due to pore plugging by cell and EPS. Abstract: Anammox granular sludge bed technology has been widely applied for its attractive advantages. Efficient mass transfer is an important factor for the anammox granules to play their role. In this study, steady-state anammox granules were used to investigate the correlation between the permeability and granule size with the granule pore as pivot. The results of size distribution showed that the anammox granules could be divided into 6 groups: 200–500 µm (I), 500–1000 µm (II), 1000–1500 µm (III), 1500–2000 µm (IV), 2000–3000 µm (V) and ≥3000 µm (VI). The results of settling experiment demonstrated that the permeability of anammox granules was negatively correlated with the granule size. The fluid collection efficiency declined from 39.4% to 9.3% for granule group I to III, and further to 0 for granule group IV to VI (granule size was larger than 1.5 mm). The observation of micro-CT revealed that the pore structure of anammox granules varied significantly with the increase of granule size, forming a denser surface layer and sparser interior. The chemical analysis and microscopic observation indicated that the pore plugging of surface layer by cell proliferation and EPS secretion was the main cause for the permeability deterioration. The findings of this study will help to understand the mass transfer of anammox granules and promote the development of anammox processes. Graphical abstract: Image, graphical abstract